Molecular characterization of a cohort of individuals referred to genetic testing with suspected CPVT. (14th October 2021) - Fernandez, G; Brogger, M.N; Garcia, S; Ochoa, J.P; De La Higuera, L; Fernandez, X; Garcia, D; Lamounier, A; Valverde, M; Cardenas Reyes, I; Ortiz, M; Monserrat, L; et al.
Abstract: Background: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is one of the most lethal inherited arrhythmogenic diseases and it mainly affects the young, in the absence of structural heart disease. This condition is difficult to diagnose and the first expression of disease can be an arrhythmic death. In the last years, genetic testing has become a useful tool in the challenging task of CPVT diagnosis. The diagnostic yield of the genetic study is highly variable and dependent on the phenotypic characteristics of the individuals evaluated. Purpose: This study aimed to address the clinical characteristics and genetic testing (GT) results in a cohort of individuals referred to genetic analysis with a non-definitive diagnosis of CPVT, in a real world-setting. Methods: This is a retrospective cohort study of patients referred for GT with clinical suspicion of CPVT, but who did not strictly meet the diagnostic criteria for this disease (according to current guidelines). NGS genotyping was performed with a library of 251 genes. NGS-based genomic testing was performed with classification of identified variants according to American College of Medical Genetics and Genomics guidelines. Results: One hundred and sixteen unrelated patients with available clinical information (patients' characteristics are summarized in TABLE1) were included in the analysis. Mean age at GT was 36 y/o (±19), 47% were women and 18% had a familial history of sudden cardiac death. The first clinical manifestation was: exercise or stress induced syncope in 36%, exercise induced ventricular tachycardia in 30% and sudden cardiac arrest in 15.5% (78% during emotional or physical stress - 89% aborted sudden death). Mean age at sudden death was 20 y/o (±14). GT was positive in 49.1% (n=57), negative in 37.9% (n=44) and inconclusive in 12.9% (n=15). We had identified pathogenic/likely pathogenic variants in CPVT-related genes in 40% of the referred patients: RYR2 (70.2%-n: 40), KCNJ2 (8.8%-n: 5), CASQ2 in homozygous/compound heterozygous carriers (3.5%-n: 2). In the RYR2 gene we detected 36 different genetic variants (13 were novel) in 40 different individuals. In addition, relevant variants were also identified in other genes associated with channelopathies (SCN5A, 3.5%, n: 2 and KCNQ1, 1.7%, n: 1) and in genes associated with structural heart disease: desmosomal genes (6.8%-DSP n: 1 and PKP2 n: 3) and sarcomeric genes (5.1%- MYBPC3 and MYH7) (figure 1A-B). Conclusions: In our cohort of patients with non-definitive diagnosis of CPVT, the diagnostic yield of genetic testing was almost 50%. GT allowed confirmation of the suspicion of CPVT in 40% of the patients and, in addition, we were able to detect relevant genetic variants in other genes not associated with CPVT in 10% (differential diagnosis). The use of wide genetic panels would be useful in this context. Funding Acknowledgement: Type of funding sources: None.